(untitled) (Journal of Nepal Geological Society, 1997)
The typical geomorphic features of a landslide such as horseshoe shaped steep scarp and debris mounds are observed adjacent to the southeastern end of the Phoksundo Lake. The mounds consist of rock detritus ranging from cobble size to boulders of several tens of meters in diameter. The total volume of the debris deposited on the left side of the Bauli Gad is estimated to be about l.5 billion m3. The Phoksundo Lake is originated due to landslide damming resulting from a mountain collapse. The detritus is overlying the glacial drift. It implies that one of the glacial valley walls became unstable after the glacial retreat and collapsed over its own glacial drift, probably triggered by an earthquake. The mountain collapse may have occurred around 30 to 40 ka, just after the early substage of the glacial advance in the Last Glacial age.